Biocompatibility Evaluation of Resin-Based Restorative Materials: A Review - Nurhan Özalp; Ceren Çimen (Ankara University, 2021)
Biocompatibility is described as an appropriate biological response of a biomaterial in a living organism. It is known that biomaterials are not inert and the materials should be tested before they are allowed to be used in clinical practice. Various test methods have been developed and protocols have been determined for this purpose. Resin-based restorative materials are extensively used in dentistry due to the increased aesthetic demands of patients and the ease of use in clinical practice. As the restorative materials function in the mouth for long years, concerns regarding the biocompatibility of resin-based restorative materials become more important. Regarding the importance of this issue, the purpose of this review is to evaluate the local and systemic potential toxicity of resin-based restorative materials, toxicity test methods, and the mechanism of the cytotoxicity in living tissues.